Geloofsvorming as saam-stappende verbondenheid - Dawid P. Mouton (Verbum et Ecclesia)
Faith formation as co-stepping covenantal accompaniment. Catechesis and other faith formation practices often focus solely on the transmission of theological and dogmatic knowledge. This approach, combined with other factors, frequently leads to adolescents disengaging from congregational activities after taking confession. Research shows that when meaningful relationships are integrated into these processes, adolescents are more likely to remain involved in their congregations even after confession. This article,1 drawing on data from a larger project on catechesis within Afrikaans-speaking congregations of the Dutch Reformed Church family, as well as a literature study, advocates for renewed emphasis on relationships during catechesis and other formation practices. The arguments presented here are centred on the concept of faith formation as a covenantal journey, and theological justifications for this are provided.